COMPARATIVIST ANALYSIS OF REPRESENTATIONS ABOUT WILL IN VIEW OF FRIEDRICH NITZSCHE AND JALALIDDIN RUMI - Tashpulatovna, , Kabulniyazova Gulchehra (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to a comparative analysis of similar ideas and ideas in the philosophy of Friedrich Nietzsche and Jalaliddin Rumi. Finding such common views can contribute to the formation of a universal, humanistic worldview that could successfully oppose fundamentalist views. We study not only concepts, but also representations, poetic images in the works of both philosophers. The article reveals that Nietzsche's superman and Rumi's perfect man are creative individuals who, with the help of unconscious will, can change themselves and the world around them.